PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI MASA PANDEMI COVID-19 (STUDI KASUS PADA STMB MULTI SMART MEDAN) - Tasya Gozali; Denni deninis (Jurnal Ekonomi Bisnis Manajemen Prima, 2022)
This study aims to determine the magnitude of the influence of organizational culture and work discipline on employee performance at STMB MULTI SMART Medan during the Covid-19 pandemic. The research methodology used is descriptive quantitative method and the nature of this research is descriptive explanatory. The type of data in this study is quantitative data. The number of samples taken is 42 people as much as the total population of employees. Types and sources of data in this study using primary data and secondary data. Data collection techniques in this study were conducted by interviewing, asking several questions and studying documentation. Based on the results of the t test or partially stated that organizational culture does not have a positive and significant effect on employee performance, while work discipline has a positive and significant effect on employee performance. The results of the F test or simultaneously stated that organizational culture and work discipline have a positive and significant effect on employee performance. The value of the determinant coefficient (R2) indicates that the independent variables, namely organizational culture and work discipline, can explain the performance of STMB MULTI SMART Medan employees amounting to 72% while 28% is influenced by other variables not included in this study.